Termofluencia en aleaciones de Fe-Mo - Rodriguez Milla, C.; Volpi, Ricardo María; Victoria, M. P. (Comisión Nacional de Energía Atómica; Argentina, 1974)
Fil: Rodriguez Milla, C. Comisión Nacional de Energía Atómica; Argentina